The role of VEGF in cancer-induced angiogenesis and research progress of drugs targeting VEGF - Ghalehbandi, Seyedehdelaram; Yuzugulen, Jale; Pranjol, Md Zahidul Islam; Pourgholami, Mohammad Hossein (Elsevier, 2023)
Angiogenesis is a double-edged sword; it is a mechanism that defines the boundary between health and disease. In spite of its central role in physiological homeostasis, it provides the oxygen and nutrition needed by tumor cells to proceed from dormancy if pro-angiogenic factors tip the balance in favor of tumor angiogenesis. Among pro-angiogenic factors, vascular endothelial growth factor (VEGF) is a prominent target in therapeutic methods due to its strategic involvement in the formation of anomalous tumor vasculature. In addition, VEGF exhibits immune-regulatory properties which suppress immune cell antitumor activity. VEGF signaling through its re-ceptors is an integral part of tumoral angiogenic approaches. A wide variety of medicines have been designed to target the ligands and receptors of this pro-angiogenic superfamily. Herein, we summarize the direct and indirect molecular mechanisms of VEGF to demonstrate its versatile role in the context of cancer angiogenesis and current transformative VEGF-targeted strategies interfering with tumor growth.
Keywords: Angiogenesis; Anti-angiogenic agents; Vascular endothelial growth factor; Anti-VEGF; Human solid cancers